2012
DOI: 10.5130/ajceb.v7i1.2975
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Barriers to Entry in the Construction Industry

Abstract: This research looks at the significance of barriers that firms considering entry into the construction industry might face. Drawing on the microeconomic characteristics of imperfectly competitive and oligopolistic markets the analysis finds that there are a dozen barriers to entry that affect the industry, but their significance depends on the product type. The discussion covers the question of product homogeneity in construction and evidence for the existence of barriers to entry in concentration levels. Barr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Non-traditional forms of procurement de Valence, 2011;Leiringer, 2006;Li and Akintoye, 2003 By avoiding traditional forms of procurement, a client has the opportunity to encourage innovative solutions. These might include public-private-sector partnerships (PPPs) and other concession projects, and build and maintain (B&M) contracts where the maintenance costs of the facility are important factors in design decisions.…”
Section: Cooperation Between Participants Of the Construction Processmentioning
confidence: 99%
“…Non-traditional forms of procurement de Valence, 2011;Leiringer, 2006;Li and Akintoye, 2003 By avoiding traditional forms of procurement, a client has the opportunity to encourage innovative solutions. These might include public-private-sector partnerships (PPPs) and other concession projects, and build and maintain (B&M) contracts where the maintenance costs of the facility are important factors in design decisions.…”
Section: Cooperation Between Participants Of the Construction Processmentioning
confidence: 99%
“…Similarly, Warszawski (1996) and Cheah and Garvin (2004) also discuss financial aspects that may act as entry barriers to new firms into construction and this is also supported by our results. The responses regarding the competitive nature of the industry also support the work of Flanagan et al (2007), Yates (1994), Warszawski (1996), and those of de Valence (2012). Hardie and Newell (2011) and Cheah and Garvin (2004) who found that regulations within the construction industry had the potential to act as barriers to entry.…”
Section: Discussion Of Resultsmentioning
confidence: 56%
“…Although there has been no research into barriers to entry for Indigenous enterprises into the construction industry, it is generally considered that the construction industry has relatively low barriers to entry (Murray and Smyth, 2011; de Valence, 2012). Evidence presented to support this view is the relatively high level of start-ups in the construction industry each year (Anikeeff and Sriram, 2008), although there is also considerable evidence that a large number of these new firms fail (Holt, 2013; Konno, 2015).…”
Section: Barriers To Entry Within the Construction Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…The immigration problem is somewhat similar to that of 'too many new firms springing up' as they both represent threat of new entrants. When there is no barrier to entry, as is the case in the construction industry, and anyone or any firm can just decide to start or stop construction works, then the market can easily be over flooded with firms, leading to tipped balances, fierce competition and insolvencies (BurtonShaw-Gunn, 2009;De Valence, 2012;Research and Markets, 2015). Using strategy as ploy to distract or deter competitors, for example reporting unregistered workers who avoid tax might increase likelihood of survival.…”
Section: Market Forcesmentioning
confidence: 99%